2022
DOI: 10.1101/2022.11.11.22282215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anatomy Segmentation in Laparoscopic Surgery: Comparison of Machine Learning and Human Expertise – An Experimental Study

Abstract: Background: Lack of anatomy recognition represents a clinically relevant risk factor in abdominal surgery. While machine learning methods have the potential to aid in recognition of visible patterns and structures, limited availability and diversity of (annotated) laparoscopic image data restrict the clinical potential of such applications in practice. This study explores the potential of machine learning algorithms to identify and delineate abdominal organs and anatomical structures using a robust and compreh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Previous studies investigating segmentation of anatomical structures have mostly focused on classification of the presence of certain organs [15] or rough localization of the detected organs using bounding boxes [33]. A recent preprint [12] describes semantic segmentation of organs based on a large-scale dataset of organ segmentations [13]. This preprint covers six organs that were also analyzed in the present work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies investigating segmentation of anatomical structures have mostly focused on classification of the presence of certain organs [15] or rough localization of the detected organs using bounding boxes [33]. A recent preprint [12] describes semantic segmentation of organs based on a large-scale dataset of organ segmentations [13]. This preprint covers six organs that were also analyzed in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, translational Artificial Intelligence (AI)-based success stories in the field of surgery are lacking and clinical applications are mostly limited to orthopedic, neurosurgical, and hepatic surgical procedures [8,9]. With regard to approaches with high translational potential in laparoscopic surgery, deep learning-based algorithms have recently been shown to identify relevant anatomical areas during cholecystectomy [10,11] and organs during laparoscopy [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it can be used to create organ detection algorithms working either with weak labels or with semantic segmentation masks, for example as a basis for further development of assistance applications 17 . Proposed training-validation-test splits as well as results of detailed segmentation studies are reported in a separate publication 18 .…”
Section: Usage Notesmentioning
confidence: 99%